Inner retinal change in a novel rd1-FTL mouse model of retinal degeneration - Greferath, Ursula; Anderson, Emily E.; Jobling, Andrew I.; Vessey, Kirstan A.; Martinez, Gemma; de Iongh, Robb U.; Kalloniatis, Michael; Fletcher, Erica L. (Frontiers in Cellular Neuroscience, 2015)
While photoreceptor loss is the most devastating result of inherited retinal degenerations such as retinitis pigmentosa, inner retinal neurons also undergo significant alteration. Detailing these changes has become important as many vision restorative therapies target the remaining neurons. In this study, the rd1-Fos-Tau-LacZ (rd1-FTL) mouse model was used to explore inner retinal change at a late stage of retinal degeneration, after the loss of photoreceptor nuclei. The rd1-FTL model carries a mutation in the phosphodiesterase gene, Pde6b, and an axonally targeted transgenic beta galactosidase reporter system under the control of the c-fos promoter. Retinae of transgenic rd1-FTL mice and control FTL animals aged 2–12 months were processed for indirect fluorescence immunocytochemistry. At 2 months of age, a time when the majority of photoreceptor nuclei are lost, there was negligible c-fos reporter (FTL) expression, however, from 4 months, reporter expression was observed to increase within subpopulations of amacrine and ganglion cells within the central retina. These areas of inner retinal FTL expression coincided with regions that contained aberrant Müller cells. Specifically, these cells exhibited reduced glutamine synthetase and Kir4.1 immunolabelling, whilst showing evidence of proliferative gliosis (increased cyclinD1 and glial fibrillary acidic protein expression). These changes were limited to distinct regions where cone photoreceptor terminals were absent. Overall, these results highlight that distinct areas of the rd1-FTL central retina undergo significant glial alterations after cone photoreceptor loss. These areas coincide with up-regulation of the c-fos reporter in the inner retina, which may represent a change in neuronal function/plasticity. The rd1-FTL mouse is a useful model system to probe changes that occur in the inner retina at later stages of retinal degeneration.